Comparison of single versus double versus triple site band ligation for haemorrhoids in a single visit: a case-controlled double blind randomized study - Dewanda, Neeraj K.; Babal, Rohit; Kumar, Harsh; Chawla, Deshraj (International Surgery Journal, 2020)
Background: Rubber band ligation is considered one of the most popular non-surgical procedures available, representing the most reasonable balance between efficacy, pain and potential of complication. The present study was a controlled double blinded randomized study to compare Single versus double versus triple site band ligation for haemorrhoids in single treatment visit with special regards to its safety and efficacy in our patient population. Methods: There were 78 patients equally randomized in three groups by closed enveloped method. The number of patients in each group was 26, In Group A, a single, in Group B, two, and in Group C three major haemorrhoidal groups were rubber band ligated, in a single treatment visit on outpatient basis under topical anaesthesia with lignocaine 2% jelly. Results: Rubber band ligation was effective with significant symptom improvement seen in all patients with 88% patient satisfaction at end of 30 days period. Post ligation pain score and number of analgesic requirement in immediate post band ligation period, at 12 hours, at 1,7,14, 21 and 30 days post band ligation were similar in all three groups with p value >0.05. Multiple site haemorrhoidal bandings was done safely at single session without severe discomfort, pain or bleeding or severe complications requiring hospitalization. Conclusions: The study finding shows that triple site band ligation in a single session is a safe way of treating symptomatic haemorrhoids with similar post-procedure pain and patient satisfaction as conventional single or double site band ligation.